Cocaine Smuggling by Help of Narco-Submarines from South America to Europe and Africa: A Proven Case – A Last Wake-Up Call for Customs Services Around the World - Carsten Weerth (Customs Scientific Journal CUSTOMS, 2020)
The drug cartels of South America and organized crime have long been known to use semi-sub speedboats, Narco-Torpedoes and Narco-Submarines for smuggling cocaine from South America to Mexico and eventually to the United States of America. The drug trade is increasing strongly and organized crime is always looking for better and smarter ways to smuggle drugs into target countries. The story started as early as 1993 and eventually it started to be a case of chain manufacture of custom-built Narco-Submarines in 2007. Counter-measures in the Americas in the war on drugs are the use of Anti-Submarine Technology such as Submarine-hunter Aircrafts, Submarines and Coast Guard Ships. Now for the first time a Narco-Submarine has been seized transporting more than 3 000 Kilogram Cocaine to Spain. Are Europe's and Africa's Customs Administrations prepared? Are Europe's and North Africa's Coast Guard forces equipped and working together in order to seize Narco-Submarines from the Americas? This is the last wake up call for a newly emerging threat to Customs Services around the World. This capacity building and background paper investigates newspaper and official reports as well as scholarly papers on the development and evolution of Narco-Submarines in Middle and South America and the current use of Narco-Submarines in Middle and South America. In particular details on new developments in the increase of their use in smuggling attempts to North America are given. In particular itinvestigates and discusses in detail the case of a proven trans-Atlantic trip of a Narco-Submarine from South America to Europe in November 2019. In conclusion this paper calls for a higher awareness and better vigilance for this novel way of irregular naval warfare and drug smuggling from Southern America to Europe and Africa by help of Anti-Submarine technology such as Anti-Submarine Aircrafts, Anti-Submarine Naval Ships and the use of naval forces such as the Coast Guard in coordinated operations in Europe and Africa in order to combat global drug smuggling.
Keywords: E26; F14; K33; K34; Q37; 330; customs technology; law enforcement; submarine detection; anti-submarine technology; irregular naval warfare; capacity building